2022
DOI: 10.1007/s10750-022-05031-3
|View full text |Cite
|
Sign up to set email alerts
|

Species depauperate communities and low abundances of monogenean gill parasites at the edge of the natural distribution range of their cichlid hosts in northern Africa

Abstract: In Morocco, no work has been carried out on parasitic monogeneans of cichlid fish. An examination of the gills of 375 fish from three native species of Cichlidae: Oreochromis aureus, Coptodon zillii and Coptodon guineensis from different localities, revealed the presence of two monogenean species (1328 monogenean specimens were recovered from 56 fish specimens) belonging to the family Dactylogyridae and to the genus Cichlidogyrus: three morphotypes of C. cirratus were identified from O. aureus and C. zillii; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The current study's low number of gyrodactylids isolated from cyprinid hosts could be due to the fact that only the gills were examined for parasites. Similarly, Louizi et al [46] found a species depauperate fauna and low abundances of gill-infecting monogeneans on native cichlid fishes in Morocco. In addition to the low prevalence and possible seasonality of members of Gyrodactylus, less research, a lack of reports on infections, a lack of understanding of relationships between these monogeneans and cyprinid hosts [14], and environmental conditions in Morocco's freshwater ecosystems might limit the species richness and abundance of certain monogenean taxa.…”
Section: Discussionmentioning
confidence: 86%
“…The current study's low number of gyrodactylids isolated from cyprinid hosts could be due to the fact that only the gills were examined for parasites. Similarly, Louizi et al [46] found a species depauperate fauna and low abundances of gill-infecting monogeneans on native cichlid fishes in Morocco. In addition to the low prevalence and possible seasonality of members of Gyrodactylus, less research, a lack of reports on infections, a lack of understanding of relationships between these monogeneans and cyprinid hosts [14], and environmental conditions in Morocco's freshwater ecosystems might limit the species richness and abundance of certain monogenean taxa.…”
Section: Discussionmentioning
confidence: 86%
“…In addition to the low prevalence and possible seasonality of members of Gyrodactylus, less research, a lack of reports on infections, and a lack of understanding of relationships between these monogeneans and cyprinid hosts [12], the current study's low number of gyrodactylids isolated from cyprinid hosts could be due to the fact that only the gills were examined for parasites. However, on native cichlid fishes in Morocco, [34] also found a species depauperate fauna and low abundances of gill-infecting dactylogyrids: hence, we cannot exclude that environmental conditions in Morocco's freshwater ecosystems limit the species richness and abundance of certain monogenean taxa. On the other hand, Dactylogyrus reaches higher species richness and higher infection intensities on Moroccan cyprinid-monogenean systems [4,35] More research is needed in the African continent to understand the relationship, evolutionary history, and development of gyrodactylids and their hosts, as it is endowed with a diverse endemic fish fauna that undoubtedly harbors undiscovered parasite diversity [36,37].…”
Section: Discussionmentioning
confidence: 88%
“…A similar case has been reported for C. cirratus Paperna, 1964, where a thin transparent structure in the MCO varies considerably. This variation was initially associated with the position of the worm on the slide [132], but recent evidence suggests the presence of three distinct morphotypes [60]. For C. ophioglossa n.…”
Section: Discussionmentioning
confidence: 99%